P558 Should we introduce early a new biological agent in patients with Inflammatory Bowel Disease after anti-TNF discontinuation due to severe anti-TNF-induced skin lesions? A multicenter cohort study. (21st January 2022) - Cottron, C; Treton, X; Altwegg, R; Reenaers, C; Amiot, A; Fumery, M; Vuitton, L; Peyrin-Biroulet, L; Bouguen, G; Dewit, O; Nancey, S; Caillo, L; et al.
Abstract: Background: Data to manage patients with Inflammatory Bowel Disease (IBD) after anti-TNF discontinuation due to severe induced skin lesions are scarce. Our study aimed to assess dermatological and IBD outcomes after discontinuation of an anti-TNF agent related to skin side effects. Methods: We conducted a multicenter retrospective study including consecutive IBD patients who discontinued anti-TNF due to induced skin lesions. Objectives were to determine factors associated with remission of induced skin lesions and with IBD relapse in patients with inactive disease at inclusion, particularly the impact of early introduction of a new biological agent within three months of anti-TNF discontinuation. Results: Among the 181 patients (134 women, 160 Crohn's disease) included in the 13 participating centers, 99 (55%) started a new biological agent within the first three months that was mainly ustekinumab in 75% of them. Remission of induced skin lesions occurred in 110 (62%) patients with a median [interquartile range (IQR)] interval of 8.0 (6.8–11.0) months since anti-TNF discontinuation. Scalp location was independently associated with a reduced risk of remission of induced skin lesions [HR 0.64 (95%CI 0.43- 0.94), p=0.02] while early biological therapy was independently associated with a higher probability of remission of skin lesions [HR 1.64 (95%CI 1.1–2.5), p=0.02]. Among the 148 patients with inactive IBD at inclusion, disease relapse occurred in 75 (51%) patients with a median (IQR) interval of 26.0(23.0–39.1) months. Survival rates without IBD relapse at 1 year were 85.8% (95%CI 77.5–94.9) in the early introduction group and 59.3% (95%CI 48.9–71.9) in the other group (p<0.01). Conclusion: Early introduction of a new biological is associated with higher probability of healing of anti-TNF-induced skin lesions and significantly reduces risk of IBD relapse.